2010
DOI: 10.1002/pen.21752
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic flow analysis of surface morphology on injection‐molded polypropylene

Abstract: The molecular orientation of a frozen layer in an injection‐molded specimen of a polypropylene–rubber blend was investigated. A typical V‐shaped pattern of birefringence was observed from the surface to the core in a crosscut section. From the comparison of the V‐patterns near the gate to the flow end, it was assumed that a frozen layer formed from the surface to a depth of 0.06 mm in a plaque (3 mm thickness) during the injection molding filling process. Numerical viscoelastic analysis of the fountain flow wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…The crystallinity stays constant inside the 100-μm depth because the crystallization temperature is expected to be higher than 123 °C. Our previous study suggested that the frozen-in orientation near the surface occurred at high temperature [19]. High orientation near the surface was also observed in this study, even if the crystallinity was low.…”
Section: Crystallization Near the Surface In Injection Moldingsupporting
confidence: 51%
See 2 more Smart Citations
“…The crystallinity stays constant inside the 100-μm depth because the crystallization temperature is expected to be higher than 123 °C. Our previous study suggested that the frozen-in orientation near the surface occurred at high temperature [19]. High orientation near the surface was also observed in this study, even if the crystallinity was low.…”
Section: Crystallization Near the Surface In Injection Moldingsupporting
confidence: 51%
“…The numerical method was the same as in the previous work [19]. We assumed dimensionless particles in the fluid and tracked their movement and deformation in the non-isothermal transient condition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the Al flakes at the center of the ND ordered perpendicular to the wall surface. In our previous study using an original 2‐D unsteady flow simulation program for a viscoelastic fluid, the formation of a frozen layer in an injection‐molded specimen was described using the fountain‐flow concept [10]. In this model, at the advancing flow front molten polymer moves from the center to the surface and is subjected to large deformation and then quenched at the cold wall surface.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, specimens with a structure of co‐continuous microlayers are fabricated by injection molding. The melt complexly flows during injection molding, which is critical in determining morphology . The molten polymer flows from the middle of the cavity towards the wall and is subjected to extensional deformation.…”
Section: Introductionmentioning
confidence: 99%